The expression of taboo in the PRESEEA corpus: sociolinguistic and geolectal patterns - Mayo Martín, Paula (Círculo de Lingüística Aplicada a la Comunicación, 2023)
The expression of taboo stems from the reflection of social interdiction in the language of the members of a speaking community. The social group establishes a series of conventions that affect its linguistic production and relate, on certain occasions, to prohibited conduct. We present a contrastive study in which we compare the results of four investigations describing the sociopragmatic phenomenon of linguistic taboo in the expression of speakers from Madrid (Cestero Mancera 2015a, 2015b and 2018), Granada (Jiménez Morales 2016), Málaga (Guerrero and Pérez 2021) and Alcalá de Henares (Mayo Martín 2022) based on the analysis of the semi-directed interviews framed in PRESEEA. We conclude that the taboo phenomenon persists in the analysed communities and we notice sociolinguistic and geolectal patterns that we consider of interest for the future research on linguistic interdiction from a variationist perspective.
Keywords: linguistic taboo; linguistic interdiction; orthophemism; dysphemism; euphemism; PRESEEA